AB0160 Effects of TOFACITINIB (CP-690, 550) on lipid biomarkers in rat adjuvant-induced arthritis (AIA) model and in patients with active rheumatoid arthritis. (23rd January 2014) - McInnes, I.; Kaplan, I.; Boy, M.; Riese, R.; Zuckerman, A.; Clark, J.; Kishore, N.; Brosnan, M.; Zwillich, S.; Bradley, J.
Abstract : Background: Tofacitinib (CP-690, 550) is a novel, oral Janus kinase (JAK) inhibitor being investigated as a targeted immunomodulator and disease-modifying therapy in rheumatoid arthritis (RA). Administration of tofacitinib to patients (pts) with RA is associated with increases in lipid moieties, including TG, LDL and HDL cholesterol. However, altered lipid parameters are associated with active inflammatory arthritis per se. Objectives: To (1) elucidate potential mechanisms whereby inflammatory- and tofacitinib-induced changes in lipid moieties occur in a rat adjuvant-induced arthritis (AIA) model and (2) explore changes in biomarkers relevant to lipid biochemistry and cardiovascular (CV) risk in pts with RA treated with tofacitinib or placebo. Methods: Rat: Rats were treated with tofacitinib 2 mg/kg, 10 mg/kg or vehicle orally on Days 7 to 18 post-AIA induction. Reverse cholesterol transport (RCT) and cholesterol synthesis were measured on Day 14. Human: CV biomarkers were evaluated in blood samples reserved during two Phase 2 studies in which placebo was compared with tofacitinib (5, 10 and 15 mg BID, specimens available from 17 to 30 pts in each group) at baseline and after 12 weeks of treatment. Results: Rat: Total plasma cholesterol, cholesterol ester (CE), rate of cholesterol esterification, plasma HDL, apolipoprotein (Apo) A-I and TG were all significantly reduced in AIA compared with non-arthritic animals. Treatment with tofacitinib dose-dependently reduced joint inflammation and increased plasma cholesterol (mostly HDL) and Apo A-I. At 2 mg/kg and 10 mg/kg, respectively, plasma CE increased by 25% - 35%. In vivo cholesterol esterification rates were enhanced by 20% - 30% via increased activity of lecithin-cholesterol acyltransferase (LCAT) to levels similar to those seen in non-arthritic rats and cholesterol excretion as neutral sterols and bile acids was increased. Paraoxonase activity, a marker of HDL anti-oxidant functionality, decreased upon arthritis induction, but was subsequently elevated by tofacitinib treatment. Human: Dose-dependent increases in total cholesterol, HDL and LDL were observed in tofacitinib groups. TG also increased with tofacitinib treatment; however there was no clear dose response. Consistent with the rodent data, tofacitinib administration increased activity of LCAT (by 38 - 62 nmol/mL/h) in 5, 10 and 15 mg BID groups and paraoxonase in 5 and 10 mg groups by 4.5 and 36 U/L, respectively. HDL associated SAA was reduced (by 40 - 60 mg/dL) at all doses, as was Lp(a) (by 3.7 mg/dL) in 15 mg BID recipients. Apo CIII was elevated (1.5 - 3.0 mg/dL) in all dose groups, consistent with the elevation in TG. No changes were observed in Lp PLA2 or CETP levels. Conclusions: AIA induction in rats provoked reduction in lipid concentrations and impairment of RCT, which was restored towards normal levels by tofacitinib. Increased LCAT and paraoxonase activities in RA pts, as well as AIA rats, combined with changes in some CV markers upon treatment with tofacitinib, may indicate structural and functional modifications in lipoprotein particles, implicating JAK dependent pathways in the biology of vascular co-morbidity. Disclosure of Interest: I. McInnes Grant/Research support from: Pfizer Inc., Consultant for: Pfizer Inc., Speakers Bureau: Pfizer Inc., I. Kaplan Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., M. Boy Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., R. Riese Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., A. Zuckerman Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., J. Clark Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., N. Kishore Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., M. Brosnan Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., S. Zwillich Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., J. Bradley Shareholder of: Pfizer Inc., Employee of: Pfizer Inc.